A "Extensão Pesqueira" no desenvolvimento das comunidades litorâneas no estado do Ceará - Silva, Jefferson Souza da (2003)
The work focuses on the relationship between the "fishing extension" that seems to us cannot be only "fishing" any more ..., and the coastal communities in the development process. Starting from the question - which sense can be given to the expression "fishing extension" considering the complexity in which the coastal communities are today inserted? - we first analyze public policies for fishing, proving that these have not been contributing to the development of the artisanal fishing, privileging, above all, the business and industrial sectors. The policies are characterized by the lack of integration; the lack of effective and qualified participation of the coastal populations in their definition and by the little importance given to environmental matters. The degradation of the environment, the dispute for ownership and use of the land and the predatory exploration of the natural resources increase the difficulties to achieve socio-environmental sustainability for the coastal communities. The communities face the challenge to increase their critical and propositive capacity, to influence in public policies, as well as to build efficient forms to produce and organize collectively. We point out that a public extension service could accomplish an important role in this process. However, considering the non-existence and/or previous errors, this service should be adjusted to the new socio-environmental framework of the new coastal world. To overcome the tecnicist and expansion order, based on conservative modernization and the mercantilization of the natural resources, of the current frameworkconstitutes a fundamental condition for the construction of this new model that will be guided by local development and social and spatial sustainability.